COVID-19 Pandemic: Stress Coping Mechanism and Preventive Measures - Aabid Hussain (AlQalam Journal of Medical and Applied Sciences, 2020)
The outbreak of coronavirus disease 2019 (COVID-19) maybe stressful for people of all ages and this ongoing COVID-19 pandemic has resulted in many quarantine and social isolation measures designed to keep individuals physically distanced from others for the foreseeable future. Although these initiatives are necessary to prevent the spread of novel coronavirus, they may be causing widespread mental health effects or psychological illness including anxiety, fear, loneliness, social phobia, hopelessness, depression, irritability, worry, anger, frustration, insomnia etc. The COVID-19 pandemic has effected all the domains of human life/personality including Mental, Physical, Social, occupational, Emotional and psychological as well and the common physical symptoms which occurs due to this pandemic are unsafe fatigue, frequent colds, nausea, chest pain, eating too much, crying a lot, smoking and drinking more than usual or physically striking out at others by hitting or throwing things and these are the clear indication of stressful life which have evoked due to COVID-19 pandemic